ASSOCIATION OF SERUM TOTAL BILIRUBIN LEVEL WITH DIABETIC RETINOPATHY IN TYPE 2 DIABETES MELLITUS - Ghaffar, Tahir; Marwat, Zahid Irfan; Ullah, Fahim; Khan, Salman; Aamir, Aziz ul Hassan (Journal of Ayub Medical College Abbottabad, 2016)
Background: Serum bilirubin has anti-inflammatory, antioxidant and immunological properties. It is considered a protective substance against atherosclerotic and microvascular complications of diabetes mellitus (DM). This study was designed to find the association between total serum bilirubin concentration and diabetic retinopathy (DR). Methods: This case control study was conducted in the Department of Endocrinology, Diabetes and Metabolic Diseases, Hayatabad Medical Complex, Peshawar. Type-2 DM patients more than 18 years of age of either gender with duration of T2DM more than 6 months were included and sub categorized in two groups. Cases (DM with DR) and Controls (DM without DR) while patients with acute and chronic liver diseases, haemolytic anaemia, history of chronic alcohol consumption, use of hepatotoxic drugs (anti-tuberculous, anti-epileptic), women on oral contraceptive pills were excluded. All participants underwent ophthalmic examination at diabetic retinopathy screening clinic followed by pre designed set of investigations. Results: A total of 152 patients, 76 cases and 76 controls were included. Serum bilirubin concentration was found inversely and independently (p 0.000) associated and inversely co related (r -0.345and p 0.000) with prevalence of DR. Cases were concentrated in the lower quartiles of serum bilirubin concentration and vice versa. Low haemoglobin (p 0.00) and longer duration of DM (0.003) were independently and directly associated with prevalence of DR. Conclusion: Serum bilirubin concentration is inversely and independently associated and inversely correlated with the prevalence of DR and may predict progression of DR over time. Keywords: Serum bilirubin; Diabetic retinopathy; Diabetes mellitus